Management Auditing as a Regulatory Tool (Book). - Tomkins, Cyril; Brief, Richard P. (The Accounting Review, 1987)
Abstract Reviews the book ""Management Auditing As a Regulatory Tool," edited by Howard H. Greenbaum.